Citrus leprosis virus cytoplasmic type 2 (CiLV-C2) detection in Meta and Casanare States - León, Guillermo; Roy, Avijit; Choudhary, Nandlal; Brlansky, Ronald (‎‎Corporación colombiana de investigación agropecuaria - AGROSAVIA, 2018)
This study discusses the diagnosis and detection of the new citrus leprosis virus cytoplasmic type 2 (CiLV-C2) in samples collected in Meta and Casanare States, using molecular techniques performed RT-PCR on plant tissue and mite vectors Brevipalpus phoenicis (Geijskes). RT-PCR tests were carry out using specific primers MP and CPG. The use of CPG primers allows the detection of CiLV-C2, in tissue plant samples with leprosis symptoms on fruits and leaves of Valencia orange (Citrus sinensis L.) and Swinglea gluinosa Merr. leaves, which confirms the presence of this virus in Colombia. The MP primers did not detect the CiLV-C2 in any of performed tests. The RT-PCR technique allows detection of CiLV-C2 in samples of B. phoenicis mite vectors, with the specific CPG primers. Molecular detection of CiLV-C2 by RT-PCR technique is a fundamental tool for the virus diagnosis in Colombia, and should be used in diagnosis and prevention programs of citrus leprosis in the country.